Using Labeling Theory as a Guide to Examine the Patterns, Characteristics, and Sanctions Given to Cybercrimes - Payne, Brian K. (American journal of criminal justice, 2019)
Over the past decade, reports of cybercrime have soared across the globe. Criminologists agree that the increase in cybercrime stems from technological advancements that have changed all facets of societal interactions. While it is agreed that technology has shaped cybercrime, there is less understanding about the dynamics of cybercrime. In particular, some researchers have explored whether these offenses are simply traditional types of crime that are now carried out through different strategies, while others have argued that cybercrimes are, in fact, new types of crime. This ambiguity potentially limits prevention and intervention strategies. In an effort to build our understanding about cybercrime within a criminological framework, in this study we use labeling theory as a guide to examine the patterns, characteristics, and sanctions associated with a sample of cybercrimes with an aim towards identifying how these offenses are socially constructed in comparison to traditional crimes, white-collar crimes, and international crimes. In doing so, our hope is to further determine how cybercrime can be understood within current criminological thinking.